Clinicopathological significance of Obg-like ATPase 1 and its association with Snail in gastric cancer - Wang, Juan; Cao, Qinghua; Wang, Zhiqing (Polish Journal of Pathology, 2023)
Obg-like ATPase 1 (OLA1) is a member of the Obg family of P-loop NTPases and has recently been detected in several human cancer cells. However, its expression type and clinical relevance in gastric cancer remains unclear. In the present study, mRNA level of OLA1 in gastric cancer (GC) was detected in 2 datasets downloaded from the open Gene Expression Omnibus database and 30 cancer tissues. Immunohistochemistry was performed on GC and its association with Snail in 334 GC patients. The results showed that OLA1 mRNA and protein were elevated in GC tissues. High expression of OLA1 was significantly associated with aggressive features, such as tumour size, lymph-node-metastasis and tumour-nodus-metastases stage ( p = 0.0146, p = 0.0037, p < 0.001, respectively). Moreover, high levels of OLA1 predicted worse overall survival. Multivariate Cox regression analysis indicated that high expression of OLA1 was an independent prognostic factor for poor overall survival ( p = 0.009). Additionally, OLA1 expression was positively correlated with Snail, and a combination of them revealed improved prognostic accuracy for GC patients. High expression of OLA1 predicts poor prognosis in GC patients and may be serviced as a novel target for GC.